Silica Sulfuric Acid as Heterogeneous and Recoverable Catalysts for the Synthesis of Dithienylmethanes under Solvent-Free Conditions - Wang, Yingling; Lu, Guangzhou; Wu, Liqiang (Asian Journal of Chemistry, 2011)
An efficient synthesis of dithienylmethanes from the reaction of thiophene and aromatic aldehydes under solvent-free conditions in good to excellent yields and short reaction times using reusable silica sulfuric acid as heterogeneous acid catalyst has been investigated.